Challenges in Indonesian Environmental Law Enforcement: Handling Individual Culpa Mistake (Negligence) Cases - Mulyono, Andreas Tedy; Sudargo, Evelina (Fakultas Hukum Universitas Lampung, 2025)
This article examines the shortcomings of environmental law enforcement in Indonesia concerning culpa (negligence) by individual offenders. Criminal sanctions in such cases often produce superficial “greenwashing” verdicts, where penalties appear strict yet fail to deliver substantive justice or environmental restoration. Although based on ecological damage assessments, these calculations rarely serve a practical function, as proving negligence becomes secondary and compensation remains unused. As a result, rulings reveal a disconnect between environmental harm and sanctions imposed, with imprisonment and fines disproportionately burdening negligent individuals while offering little ecological benefit. Using a normative juridical approach combining statutory, conceptual, and case analyses, this study finds that the system fosters inefficiency, with costly assessments underutilized and appeals largely abandoned, leaving clemency as the only viable remedy. It argues that community service sanctions focused on ecological rehabilitation would provide a fairer, more feasible, and future-oriented alternative that aligns accountability with environmental recovery.